1985
DOI: 10.1073/pnas.82.10.3301
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type-specific receptors for alpha-fetoprotein in a mouse T-lymphoma cell line.

Abstract: Binding and uptake of a-fetoprotein (AFP) by mouse T-lymphoma YAC-1 cells exhibited the characteristics of receptor-mediated endocytosis. The (2,3). On the other hand, AFP can be localized during ontogenic development in practically all tissue derived from the three embryonic germ layers (4). The intracellular presence of AFP in fetal tissues other than the liver and the yolk sac is due to active uptake of the protein (5, 6) and not local synthesis (3, 7). It has also been shown that the ability to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 28 publications
4
48
0
Order By: Relevance
“…Many investigations have shown that AFP receptors exist on the membrane of various tumor cells [5,7,8,[11][12][13] , and play an important role in regulating growth of the cells [7,8,14] . The receptor may mediate intercellular signal transduction which influences the expression of genes related to proliferation, and the expression of these genes is the most direct factor that controls cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have shown that AFP receptors exist on the membrane of various tumor cells [5,7,8,[11][12][13] , and play an important role in regulating growth of the cells [7,8,14] . The receptor may mediate intercellular signal transduction which influences the expression of genes related to proliferation, and the expression of these genes is the most direct factor that controls cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Moroianu et al [26] have reported that albumin-binding proteins are present in all fetal organs and in adult tissues characterized by active renewal, in contrast with mature cells. AFP may compete with albumin for binding in different cell types [15,[27][28][29]. Cytochemical and kinetic studies, carried out in several tumoral cells as well as in normal human T lymphocytes [18,27,30,31] have shown that the AFP was taken up by a receptor-mediated endocytosis mechanism similar to that reported for transferrin [19,28,31].…”
Section: Introductionmentioning
confidence: 96%
“…Uriel been demonstrated the specific uptake ofAFP by certain malignant cells (3)(4)(5). They have shown kinetic analysis for putative receptors on blast transformed lymphocytes as well as on a murine T lymphoma cell line, but not on normal resting lymphocytes (6,7). In these reports, the authors suggested that AFP and AFP receptors may regulate the transfer of polyunsaturated fatty acids into cells undergoing growth and proliferation.…”
Section: Introductionmentioning
confidence: 99%